First record of a spiral form of Aulacoseira, A. ambigua f. japonica (F.Meister) Tuji & D.M.Williams, in South African fresh waters. Issue 4 (15th December 2016) - Janse van Vuuren, S; Taylor, JC
Abstract : Water quality and algal populations in the Vaal River Barrage Reservoir have been monitored extensively for many decades, because of its importance as a water source for the most densely populated area in South Africa. Although Aulacoseira granulata (Ehrenberg) Simonsen is frequently found and at it times dominates algal assemblages in the Barrage, Aulacoseira ambigua (F.Meister) Tuji & D.M.Williams has never before been recorded at this locality. During a countrywide proficiency-testing scheme for algae counting, coordinated by Rand Water, spiral-shaped diatom colonies with distinctly curved cells were detected during May 2015. Upon investigation, it was found that the spiral colonies were Aulacoseira ambigua f. japonica, its presence in the fresh waters of South Africa being recorded for the first time. Since their first appearance during May 2015, colonies of Aulacoseira ambigua f. japonica have been constantly present in the surface waters of the Barrage. Their presence at this site can be linked to increasing eutrophication in the Vaal River, because the spiral form is known to prefer eutrophic conditions. Centric diatoms rarely form spiral colonies and there is some confusion in the literature as to the identity of this particular form, therefore in this paper we discuss this taxon, its nomenclature and ecological significance.